The Influence of Netspeak on the University Students’ Language Learning When Using Chinese Social Media Network - Ruan, Banshengnan (Trinity College (Dublin, Ireland). School of Education, 2022)
This study aims to study the influence of Netspeak on university students' language learning in Chinese Network. Netspeak is a term that describes one particular type of language used in internet communication. Thangaraj and Maniam (2015, p. 45) stated that Netspeak is a fixture in language, which is acknowledged for its passing style and momentary trend, which means Netspeak is not mainstream culture and is only a fad, they are constantly emerging. Even if some Netspeak disappears, the patterns of thinking that people form after using them are deep-rooted in the long run; they will inevitably affect the way of thinking. The research aims to study the following three questions; 1) How does Netspeak influence University students? 2) What are the attitude of students using Netspeak? 3) What’s the impact of Netspeak on University students’ language learning and writing skills? The participants of this study are 196 University students who speak Chinese as their first language, mainly between 18-24 years old. They come from 112 universities in 12 countries, including Ireland, Australia, Germany, America, Netherlands, Korea, France, Switzerland, Malaysia, England, Hong Kong (China), and 4 Municipalities directly under the Central Government and 23 provinces in China. The study is mainly quantitative in nature, using the Statistics Package of Social Sciences (SPSS) and Quantitative content method to analyze data. The research data was collected through questionnaires with a combination of three sampling strategies, including convenience, snowball, and volunteer sampling strategies. After analysis of the non-open-ended questions, the research findings indicated a positive interrelationship between university students' high frequency of using Netspeak daily and their high tolerance toward Netspeak. Meanwhile, university students' high frequency of using Netspeak in daily life, high tolerance towards Netspeak, and knowing much about the trend of Netspeak would make it easier for them to switch between formal/standard Chinese and Netspeak. This will also result in reasonable compliance with the grammatical rules in their writing process. After analysis of two open-ended questions, the research finding indicated their positive and negative attitude toward Netspeak aspects, the decline or rise of the qualities of articles written by students, and students'' personal abilities. The findings of this study underline the need for recommendations to university students about their ability to distinguish and use Netspeak in their writing process and positive attitude in accepting the trend of the development of Netspeak awareness of protecting national language while being good examples and leaders for other groups of people.
Keywords: Language Education; Education